The Use of Sixty Degree Rotation of the Acetabulum for Treatment of Dogs With Canine Hip Dysplasia. A Short Case Series - Elefterescu, Horia; Ober, Ciprian Andrei; Timen, Andrei; Yiapanis, Christos; McCartney, William; Milgram, Joshua (Frontiers in Veterinary Science, 2021)
Triple pelvic osteotomy (TPO) is a prophylactic surgical procedure performed on dogs with canine hip dysplasia. The procedure is indicated in skeletally immature dogs without secondary osteoarthritis (OA). It has been suggested that 60° of rotation is excessive and is associated with poor outcome. The objective of the study was to assess the medium term outcome in dogs having undergone triple pelvic osteotomy (TPO) using 60° dedicated plates. Nine TPOs were performed in seven dogs with hip dysplasia. Eight of nine hips had 72-100% osseous union at the time of revisit. The mean time to final radiographic recheck was 200 days (range, 185–229 days). The mean time to follow-up was 11.5 months (range 11–12 months). All 7 dogs had regained full function and did not require supplemental analgesia. Pelvic canal narrowing was noted in the two dogs with bilateral surgeries, but no clinical consequences were noted according to owner’s statement.If more than 40 degrees reduction angles at Ortolani test, 60° of rotation of the acetabulum can be used successfully in dogs with hip dysplasia. At the time of mid-term follow-up, all dogs in this case series had full function.